'Bridging the Gap'? Public and Private Regulation of Labour Standards in Apparel Value Chains in Brazil. (August 2014) - Posthuma, Anne; Bignami, Renato
This article contributes insights to the emerging literature on the potential interaction between corporate social responsibility (CSR) and public regulation of labour standards in global and national value chains. Based on a case study of an endogenous CSR initiative recently introduced by the Brazilian Association of Apparel Retailers (ABVTEX), the article explores how this incipient experience may offer the potential to bridge two prevalent regulatory gaps in value chains. First, communication is being fostered gradually between a private sector audit programme and the public labour inspection, pointing toward ways in which private and public action can play complementary roles in the promotion of labour standards in value chains. Second, the design of this CSR initiative seeks to extend monitoring beyond first-tier suppliers to identify vulnerable workers in subcontracted firms at lower tiers within value chains, in response to a response to a commission report of the São Paulo City Council, which advised that retailers cannot use clauses in supplier contracts to outsource responsibility for labour standards in their value chains.